Seasonal adjustment of primary and secondary growth in maritime pine under simulated climatic changes - Vieira, Joana (2019)
Key message Reducing irrigation by up to 75% in spring decreased primary and secondary growth in Pinus pinaster Aiton saplings, whereas an extra irrigation in September prompted secondary growth, confirming the high plasticity of xylogenesis in this species. Context Water availability is the main limiting factor for plant growth and forest productivity in drought-prone environments, such as the Mediterranean region. Future scenarios for this region predict an increase in spring drought and in autumn precipitation. Understanding how tree growth responds to these conditions is imperative to anticipate forest productivity shifts under future climate change scenarios. Aims We simulated the expected climatic conditions for the Mediterranean region in order to study the response of primary and secondary growth in maritime pine (Pinus pinaster Aiton) saplings. Methods In February 2017, 2-year-old maritime pine saplings (n = 512) were subjected to a water manipulation experiment in a tunnel greenhouse. Saplings were randomly divided into four groups: control, exclusion, irrigation and exclusion—irrigation. Between May and August, saplings in the exclusion and exclusion–irrigation groups received 50 to 75% less water than saplings in the control and irrigation groups. In September, saplings in the irrigation groups received an extra irrigation. From February 2017 to February 2018, primary (height) and secondary growth (diameter and wood formation) were monitored. Seasonal dynamics of cambial activity and wood formation were monitored monthly through destructive sampling. Results Primary and secondary growth were reduced in exclusion saplings. The extra irrigation in September triggered the production of tracheids with wider lumen diameter at the end of the tree ring. Conclusion Maritime pine saplings survived an intense spring drought, despite primary and secondary growth reduction. The extra irrigation in September triggered a rapid increase in cambial activity, demonstrating the high plasticity of xylogenesis in this species.